Regulatory effects of Lycium Barbarum polysaccharides on immune function and their application prospects - Li, Dan; Jin, Jing (Frontiers in Immunology, 2025)
Lycium barbarum, as a traditional medicinal plant, contains abundant bioactive components, particularly Lycium barbarum polysaccharides (LBP), which demonstrate broad application prospects in immunomodulation, anti-aging, antioxidant, antitumor, and anti-inflammatory activities. Recent years have witnessed significant progress in research on LBP’s immunomodulatory effects, demonstrating its capacity to enhance immune function through regulating immune cell activities and suppressing inflammatory responses. LBP also exhibits notable preventive and therapeutic effects against various immune-related diseases including rheumatoid arthritis, hepatic encephalopathy, and diabetic nephropathy. Furthermore, as a natural prebiotic, LBP could modulate gut microbiota composition, improve intestinal health, and consequently exert systemic immunoenhancing effects. Despite its tremendous potential in disease prevention and treatment, LBP still faces certain limitations, particularly in extraction technologies and clinical research. This review summarizes recent advances in LBP’s immunomodulatory research, with emphasis on its mechanisms of action, reveals its potential value and application prospects in immune regulation, and provides recommendations for future research and development.